Keamanan Sistem Login Menggunakan Multifactor Authentication dan Algoritma Hashing - Fitriyani, Aida; Lubis, Hendarman; Yaddarabullah, Yaddarabullah; Sari, Rafika (Journal of Information System, Informatics and Computing, 2025)
Login system security is a crucial aspect in digital application development to protect user personal data. This research aims to implement a modern hashing algorithm, Argon2, and add a security layer through Multi-Factor Authentication (MFA) using One-Time Password (OTP) codes. The Argon2 algorithm was chosen because it is memory-hard, configurable, and more resistant to brute-force attacks and rainbow table attacks. The system development method used is the Waterfall method, where the system is developed using the Kotlin programming language with the Jetpack Compose architecture, and the Firebase Authentication and Firestore databases. An OTP is sent to the user after successful registration as additional verification. Implementation results show that the time cost parameter in Argon2id significantly affects hashing execution time, with higher values improving security while remaining within performance tolerances. The combination of Argon2 and MFA successfully provides a more secure login system and is more resilient to cyberattacks than traditional authentication methods. Test results indicate that the Time Cost parameter in Argon2id significantly impacts hashing time. With the following configurations: Time Cost = 1 → 2.028 ms, Time Cost = 2 → 48.623 ms, and Time Cost = 3 → 71.219 ms. Higher parameter values increase execution time but also increase resistance to brute-force attacks. The combination of the Argon2 algorithm and MFA methods results in a more secure and reliable login system than traditional authentication, while remaining responsive in application performance.